Egyptians : facts, things to make, activities - Wright, Rachel (London : Franklin Watts, 2001)
Provides facts about life in ancient Egypt, and includes illustrated, step-by-step instructions for related craft projects and activities.
6.2
3-6
Keywords: Handicraft -- Juvenile literature; Handicraft; Handicraft; Egypt -- Civilization -- To 332 B.C. -- Juvenile literature; Egypt -- Civilization -- To 332 B.C.; Egypt -- Civilization